Barriers and facilitators of using mobile devices as an educational tool by nursing students: a qualitative research - Nasrin Nikpeyma (BMC, 2021)
Abstract Background Although the use of mobile devices can facilitate the learning process, there may be barriers to using them for learning purposes. This study aimed to identify and investigate the barriers and facilitators of using mobile devices as an educational device from the perspective of nursing students. Methods This qualitative descriptive study was conducted in 2020 on undergraduate nursing students of the Nursing and Midwifery Faculty, Tehran University of Medical Sciences. A total of 22 undergraduate nursing students were selected by purposive sampling with maximum variability. Inclusion criteria were Undergraduate nursing education, having mobile devices, and willingness to participate in research. Data were collected through semi-structured individual interviews for 45–75 min in the proposed environment of students until the data were saturated. Data analysis was performed manually using the framework analysis method with the steps: familiarization, identifying a thematic framework, indexing, Charting and Synthesis, Mapping, and Interpretation. Trustworthiness was determined by methods of Credibility, Dependability, Conformability, and Transferability. Results The majority of participants (45.45%) were 21 years old, 63.63% were women, and 36.36% studied in the 8th semester. Findings from the analysis of interviews showed that barriers to the use of mobile devices were classified into 4 main categories (barriers related to mobile devices, barriers related to Internet access, barriers related to information literacy, cultural-environmental barriers) and 15 subcategories, and facilitating the use of mobile devices was divided into 2 main categories (easy to use mobile devices and easy access to information) and 6 subcategories. Conclusion The results of this study help educational managers and curriculum planners to adapt to technological change, to focus on the many benefits of mobile devices as an educational tool, and to plan to overcome barriers to mobile device use, and use mobile devices to teach theoretical topics and clinical nursing skills effectively.